Environmentally Significant Behaviour in the Czech Republic : Energy, Food and Transportation - Ščasný, Milan; Urban, Jan, 1953-; Zvěřinová, Iva (Karolinum, 2013)
This book strives to present the results of research into the consumption of goods and services in Czech households. The first two chapters focus on the effect of consumption on the environment and theoretical approaches towards consumption and behaviour analysis. The remaining five chapters look into consumer behaviour and its significant effect on the environment, such as a demand for energy and transport, energy-saving measures in households, car ownership and organic food consumption. This book aims to point out the environmental effects related to these types of behaviour and provide new.